Does contract farming improve welfare? A review. (December 2018) - Bellemare, Marc F.; Bloem, Jeffrey R.
Highlights: We review the empirical literature on the welfare effects of contract farming in developing countries. We highlight the methodological weaknesses that limit much of the literature to date. Important factors leading to considerable heterogeneity across contexts limits external validity. Vexing issues relating to the credible causal identification of treatment effects limits internal validity. We conclude with a discussion of where we see the literature on contract farming going in the future. Abstract: Although many urban areas around the world have grown steadily in recent years, the structural transformation, wherein an economy goes from relying primarily on agriculture and natural resources to relying primarily on manufacturing, has eluded many developing countries. In those countries, contract farming, whereby processors contract out the production of some agricultural commodity to growers, is often seen as a means of spurring the development of an agribusiness sector, and thus launch the structural transformation. As a result, economists and other social scientists have extensively researched contract farming over the last 30 years. We review the findings of the economics literature on contract farming and discuss its implications for development policy and research. In so doing, we highlight the methodological weaknesses that limit much of the literature on contract farming in answering questions of relevance for policy. Despite valiant research effort, many of the core features of contract farming imply substantial challenges for researchers aiming to study the question "Does contract farming improve welfare?" We conclude with a discussion of where we see the literature on contract farming evolving over the next few decades.